Selected Albums and Tracks of Morocco Maduka - Oloko, Patrick; Kibora, Ludovic (Rethinking the "Informal" and Mainstreaming African Popular Arts and Entertainment, 2021)
Selected albums and tracks of Morocco Maduka of Rethinking the Informal and Mainstreaming African Popular Arts and Entertainment
Keywords: Arts; Aesthetics; Music; Scholars; African Studies; Popular Music Studies; African Music; Cultural Economy